Beneficial effect of Xuebijing against Pseudomonas aeruginosa infection in Caenorhabditis elegans - Zhang, Le; Wang, Yuxing; Cao, Chang; Zhu, Yike; Huang, Wei; Yang, Yi; Qiu, Haibo; Liu, Songqiao; Wang, Dayong (Frontiers in Pharmacology, 2022)
In the clinical intensive care units (ICU), the traditional Chinese medicine (TCM) formulation of Xuebijing has been frequently used for treating sepsis. Nevertheless, the underlying pharmacological mechanisms of Xuebijing remain largely unclear. Caenorhabditis elegans is an important experimental host for bacterial infections. Using C. elegans as an animal model, we here examined the potential of Xuebijing treatment against bacterial infection and the underlying mechanisms. Xuebijing treatment could inhibit the reduction tendency of lifespan caused by Pseudomonas aeruginosa infection. For the cellular mechanisms of this antibacterial infection property, we found that Xuebijing treatment rescued C. elegans lifespan to be against P. aeruginosa infection by inhibiting Pseudomonas colonization in the intestinal lumen. Meanwhile, the increase in the expression of antimicrobial genes induced by Pseudomonas infection was also suppressed by Xuebijing treatment. Moreover, the beneficial effect of Xuebijing against Pseudomonas infection depended on insulin, p38 MAPK, Wnt, DBL-1/TGF-β, ELT-2, and programmed cell death (PCD)-related signals. Although Xuebijing did not show obvious antibacterial activity, Xuebijing (100%) treatment could inhibit the Pseudomonas biofilm formation and decrease the expression of virulence genes (lasA, lasB, rhlA, rhlC, phzA, phzM, phzH, and phzS) and quorum sensing (QS)-related genes (lasI, lasR, rhlI, rhlR, pqsA, and pqsR). Our results support the potential role of Xuebijing treatment against bacterial infection in hosts.